THE EFFECT OF INFLUENCERS ON PURCHASE DECISIONS IN XINONABOBA KAPUAS, BENGKULU CITY - Chandra Sahputra; Vethy Octaviani; Yanto Yanto (Universitas Dehasen Bengkulu, 2023)
This study aims to determine the influence of influencers on purchasing decisions at Xinonaboba Kapuas, Bengkulu City. This research uses quantitative research methods. Data collection techniques were carried out using a questionnaire. The number of respondents in this study were 93 consumers who shopped at Xinonaboba Kapuas, Bengkulu City and the data analysis technique used simple linear regression techniques and hypothesis testing. The results showed that the regression value Y = 14.904 + 0.386X Â¬ with a positive regression direction, meaning that if the influencer increases, the purchase decision at Xinonaboba Kapuas Bengkulu City will also increase. Influencers have a significant influence on purchasing decisions of Xinonaboba Kapuas, Bengkulu City, because a significant value of 0.000 is less than 0.05. This means that the more influencers increase, the purchasing decision of Xinonaboba Kapuas, Bengkulu City will also increase.